Is physician dismissal of vaccine refusers an acceptable practice in Canada? A 2018 overview. Issue 2 (1st October 2018) - MacDonald, Noni E; Harmon, Shawn; Dube, Eve; Taylor, Beth; Steenbeek, Audrey; Crowcroft, Natasha; Graham, Janice
Abstract: Despite robust evidence that routine immunization is effective and safe, some parents refuse some or all vaccines for their children. In 2007, concern that Canadian paediatricians and family physicians might be considering dismissal of vaccine refusers from their practices prompted an ethical, legal, and public health analysis which concluded that dismissal was professionally problematic. We now reassess this important issue in the Canadian context updating ethical, legal, and public health considerations highlighting changes since 2007. In light of the recent strengthening of Ontario's school immunization requirements that include stiffer steps to qualify for a medical, conscience, or religious belief exemption, physicians and health care workers may be under more pressure from vaccine refusers in their practice leading some to contemplate dismissal or even consider no longer offering immunizations at all in their practice. Given the challenges that vaccine refusers may present, we offer an overview for managing vaccine refusal by parents/patients in a medical practice.